Rebirth of the clinic : places and agents in contemporary health care - Patton, Cindy, 1956- (University of Minnesota Press, 2010)
From physical location to payment processes to expectations of both patients and caregivers, nearly everything surrounding the contemporary medical clinic's central activity has changed since Michel Foucualt's Birth of the Clinic . Indebted to that work, but recognizing the gap between what the modern clinic hoped to be and what it has become, Rebirth of the Clinic explores medical practices that shed light on the fraught relationship between medical systems, practitioners, and patients. Combining theory, history, and ethnography, the contributors to this volume ground today's clinic in a larg.